2011
DOI: 10.3109/09553002.2011.584939
|View full text |Cite
|
Sign up to set email alerts
|

Neutrons do not produce a bystander effect in zebrafish irradiated in vivo

Abstract: The results confirm in vitro experiments which suggest neutrons do not induce bystander signaling. In fact they may suppress gamma induced signaling suggesting a possible intriguing new and as yet unclear mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…radiation (Salbu et al, 2008;Smith et al, 2011), as radiation types found to induce a bystander effect in fish. Neutrons have a direct effect on zebrafish but do not induce a bystander effect (Wang et al, 2011). The shift, with time, from a pro-to anti-apoptotic bystander effect and then back to a pro-apoptotic effect on HPV-G reporter cells (as seen here) could suggest the existence of a precise mechanism in bystander effect induction.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…radiation (Salbu et al, 2008;Smith et al, 2011), as radiation types found to induce a bystander effect in fish. Neutrons have a direct effect on zebrafish but do not induce a bystander effect (Wang et al, 2011). The shift, with time, from a pro-to anti-apoptotic bystander effect and then back to a pro-apoptotic effect on HPV-G reporter cells (as seen here) could suggest the existence of a precise mechanism in bystander effect induction.…”
Section: Discussionmentioning
confidence: 50%
“…Previously this assay has been shown to strongly correlate with apoptosis related bcl-2 and cmyc expression (Mothersill et al, 2007;Smith et al, 2011). In addition bcl-2 and cmyc expression in cells from irradiated and bystander fish explants has been shown to mirror bcl-2 and cmyc expression in HPV-G cells (Mothersill et al, 2009) and apoptotic bodies in irradiated fish explant cells mirrors HPV-G survival (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Most bystander effect studies have been performed using x-rays [22], [24], [29], gamma rays [17], [35], [53] and alpha particles [47], [54], [55], however, little has been done concerning the effects of neutron radiation [56]. Such information might be important for risk estimation in response to neutron exposure.…”
Section: Introductionmentioning
confidence: 99%
“…No conclusive cytogenetic evidence exists to support or refute the existence of non-targeted effects in cellular responses to neutrons. A bystander effect following neutron exposure has been observed in Chinese hamster ovary cells [57], but no effect was seen in zebrafish irradiated in vivo [56]. There are no available cytogenetic data concerning the bystander effect in human cells in response to neutrons.…”
Section: Introductionmentioning
confidence: 99%